FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI TEKNOLOGI SISTEM TANAM BENIH LANGSUNG (TABELA) PADA USAHATANI PADI SAWAH DI DESA KUKULURI KECAMATAN ANGGOTOA KABUPATEN KONAWE - Muhammad Al-hady Nasrun; Yani Taufik; Putu Arimbawa; La Nalefo (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
This study aims to determine the factors that influence the adoption of TABELA system technology in lowland rice farming in Kukuluri Village, Anggotoa District, Konawe Regency. Determination of research locations purposively. The population in this study were farmers in lowland rice farming activities in Kukuluri Village. Determination of the sample was carried out using a proportional random sampling technique of 62 people. Data analysis by logistic regression. The results showed that the factors of land area, productivity and acceptance had a significant and significant effect on the adoption of the TABELA system technology in lowland rice farming in Kukuluri Village. While the labor factor of farm laborers and family labor has no effect and is not significant on the adoption of the TABELA system technology in swah rice farming in Kukuluri Village, Anggotoa District, Konawe Regency.